Air Quality and Sustainable Development of Urban Agglomerations in the Mediterranean Area: Science, Technology and Policies - Fabio Murena; Pietro Salizzoni (Atmosphere, 2021)
Air quality in urban areas is one of the main challenges of sustainable development [...]